(untitled) (Journal of Universal Science Research, 2023)
The global food problem is one of the oldest problems of humanity. The problem of food shortage and the resulting famine has been considered one of the greatest threats to humanity both in ancient times, in the Middle Ages, and at the present time. Famine can be manifested in two forms. In the first form, famine continues chronically, as a result of which people’s health deteriorates, their skin dries up, and the possibility of contracting various diseases increases. This form of starvation is also called "not eating enough food". The second form is the death of millions and tens of millions of people at a certain time in a certain area of the earth’s surface due to drought or famine for other reasons. the ever-increasing unrest and other problems related to the human factor cause the issue of food to be on the agenda. Of course, the value of the blessing called food cannot be measured and compared with anything Therefore, preventing this problem, solving it in time, and determining the future fate of mankind is of great importance.